Environmental Issue in the Caucasus Mountains: Prospects for Solving the Issue - BAGIROV, Huseyngulu Seyid oglu (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
The modern stage in the development of civilization is characterized by the growth of contradictions between society and nature. In this regard, the study, the assessment, and the protection of biological and current landscape diversity have become a serious global environmental issue. The search for solutions is not merely an item of theoretical significance, but also great practical importance. This is not only a matter of the increasing pressure on various components of the anthropogenic environment and even on an entire ecosystem. At the same time, particularly regarding reform, there has been a clear shortage of theoretical and experimental studies of ecological systems at the regional and local levels. The Caucasus is noted for its high biodiversity and is among 200 priority regions. The North Caucasus is an integral part of the whole Caucasus, and currently is one of Russia’s most densely populated and developed regions. The region is facing a serious problem of developing a set of measures to maintain biological diversity, preserve biological resources, as well as optimize environmental management. Contemporary international studies (for example, the Johannesburg Memorandum, 2002) do not provide adequate tools for achieving the ideals of sustainable development, especially from a regional perspective. Classical ecology makes it possible to identify and formulate problems that threaten biodiversity. However, realistic and constructive proposals for their implementation have not yet been developed. The purpose of the study is to assess the current state of the ecosystems of the Caucasus Mountains for the development of ecological networks as the basis for the conservation of biological diversity.